Organocatalytic Enantioselective Vinylogous Henry Reaction of 3,5-Dimethyl-4-nitroisoxazole with Trifluoromethyl Ketones - Jafari, Ehsan; Kundu, Dipti S.; Chauhan, Pankaj; Gajulapalli, V. P. Reddy; von Essen, Carolina; Rissanen, Kari; Enders, Dieter (Synthesis, 2018)
The enantioselective vinylogous Henry reaction of 3,5-dimethyl-4-nitroisoxazole with trifluoromethyl ketones employing a bifunctional squaramide organocatalyst has been developed. A series of isoxazole bearing trifluoromethyl-substituted tertiary alcohols, 2-substituted (R)-1,1,1-trifluoro-3-(3-methyl-4-nitroisoxazol-5-yl)propan-2-ols, were obtained under these mild reaction conditions in good yields and moderate to good enantioselectivities
Keywords: asymmetric synthesis; isoxazole; trifluoromethyl ketone; squaramide organocatalyst; vinylogous Henry reaction